Iraq ICT Situation and its effect on Iraq Rebuilding: Study, Analysis, and Suggestion - Saad A. R. MAKKI; Yaakob K. HANNA (Journal of Madenat Alelem University College, 2011)
Information and Communication Technology (ICT) provides developing nations with an unprecedented opportunity to meet vital development goals, such as poverty reduction, basic healthcare, and education, far more effectively than before. In this paper, a general survey to ICT statistics in Iraq will be studied and an analysis and a comparison between ICT statistics in Iraq, Arabian and Developing countries will be performed. In addition, a statistical result from a USA and European Countries will be performed for comparison purposes. Suggestions will be presented to reach the required level of ICT in Iraq to enable the process of Iraqi rebuilding. These suggestions include the requirements from educational, governmental, and private sector activities.